Islamic Religious Education Learning Innovation at the MTsN Model Banda Aceh and the MTsN Model Gandapura Bireuen - Fakhrul Rijal; Burhan Nudin; Iskandar Abdul Samad (STAI Hubbulwathan Duri, 2022)
This study aims to determine the elements of learning innovation, differences and similarities, as well as candidates for Islamic religious education learning innovations in two Model MTsN of Aceh province. This research method uses a qualitative approach. Data collection techniques include in-depth interviews, observation, and documentation. The data was then analyzed by descriptive analysis consisting of data reduction, data presentation, and drawing conclusions. The results showed that: 1) The innovation of Islamic religious education learning at the two MTsN models was carried out through the enrichment of the Islamic religious education curriculum, which included sharpening, remedial, and coaching programs. At MTsN Model Aceh, learning innovation also includes a variety of methods, from monotonous to varied, and from lectures to discussions, exercises, assignments, homework and presentations. The innovation of Islamic religious education learning media in the Aceh MTsN Model also varies from manuals to digital media, from worksheets to e-learning media, and from classrooms to laboratories. Furthermore, the learning evaluation innovation in the Aceh MTsN Model consists of tests and non-tests; 2) The similarity of Islamic religious learning in both the Banda Aceh Model MTsN and the Gandapura Model MTsN in terms of curriculum enrichment lies in the use of the National curriculum standards. On the other hand, the difference lies in class grouping, where the Banda Aceh Model MTsN makes small groups and the Gandapura Model MTsN makes a package system.